1969
DOI: 10.5912/jcb224
|View full text |Cite
|
Sign up to set email alerts
|

Building a conducive environment for life science-based entrepreneurship and industry clusters

Abstract: The global biopharmaceutical industry, with over $70bn in revenues and 700 publicly listed firms posting double-digit growth in North America, Europe, and Asia-Pacific in 2006, represents an attractive and promising high-growth industry of the future. Broad scientific advances and commercial successes have captured the attention and aspirations of policy makers, business people, and investors alike in spurring sector growth. An understanding of the fundamental forces that shape the industry, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…( 59 ) Consider, for example, the biotechnology industry, which is perceived to possess high levels of product and regulatory risk. ( 60 ) Another explanation may lie with the fact that perceived levels of risk are associated with the experience and maturity of the project manager, organization, and industry. Maturity models, which evaluate the overall effectiveness of organizational processes, ( 57 ) have found that construction and engineering organizations have the highest levels of maturity.…”
Section: Discussionmentioning
confidence: 99%
“…( 59 ) Consider, for example, the biotechnology industry, which is perceived to possess high levels of product and regulatory risk. ( 60 ) Another explanation may lie with the fact that perceived levels of risk are associated with the experience and maturity of the project manager, organization, and industry. Maturity models, which evaluate the overall effectiveness of organizational processes, ( 57 ) have found that construction and engineering organizations have the highest levels of maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Resources can be classified in different ways (Chetty & Wilson, ; Gassel & Pascha, ; Tolstoy & Agndal, ; Wei & Clegg, ), this study employs the same classification Tolstoy and Agndal () developed: market, human, reputational, financial, physical, and technical resources. Their classifications were derived from other studies in the biotech industry (e.g., Ahn & Meeks, ; Gassel & Pascha, ; Powell, Koput, & Smith‐Doerr, ). As this study focuses on firms from the health‐technology sector, it is reasonable to argue that the same classification is meaningful also in this study.…”
Section: Resources and Internationalizationmentioning
confidence: 99%
“…Within the context of the economic mega-forces of information technology, biotechnology, and global capital markets, as well as a heavy reliance on primary industries and associated commodity pricing risk [Ahn and Meeks (2007); McKinsey (2004); NZVCA (2007)], there is a general consensus that New Zealand needs to evolve toward a higher value-added economy to experience sustainable economic growth and enhance standards of living [Clark (2002); FRST (2007); MoRST (2007,2008)]. High growth¯rms, such as the elite group of Deloitte/Unlimited Fast 50 representing the fastest growing set of¯rms in New Zealand, embody this hoped-for evolution [Unlimited (2008)].…”
Section: Emerging Challenges For High-growth¯rms In New Zealandmentioning
confidence: 99%